2021
DOI: 10.1111/1462-2920.15662
|View full text |Cite
|
Sign up to set email alerts
|

Lysobacter enzymogenes antagonizes soilborne bacteria using the type IV secretion system

Abstract: Summary Soil microbiome comprises numerous microbial species that continuously interact with each other. Among the modes of diverse interactions, cell–cell killing may play a key role in shaping the microbiome composition. Bacteria deploy various secretion systems to fend off other microorganisms and Type IV Secretion System (T4SS) in pathogenic bacteria was shown to function as a contact‐dependent, inter‐bacterial killing system only recently. The present study investigated the role played by T4SS in the kill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(50 citation statements)
references
References 70 publications
(141 reference statements)
4
46
0
Order By: Relevance
“…A recent study showed that L. enzymogenes OH11 employed T4SS as the main contact dependent weapon to suppress other soilborne bacteria. The T4SS-mediated killing behavior of strain OH11 was proven to be essential to inhibit the plant pathogenic bacterium P. carotovorum ( Shen et al, 2021 ). In this study, the virB/D T4SS was present in the conserved genetic organization in L. enzymogenes strains CX03, CX06, M497-1 and C3, which indicated that the T4SS may play a vital role in the antagonistic activities of the bacterium; however, further studies need to explore the function of T4SS in L. enzymogenes .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that L. enzymogenes OH11 employed T4SS as the main contact dependent weapon to suppress other soilborne bacteria. The T4SS-mediated killing behavior of strain OH11 was proven to be essential to inhibit the plant pathogenic bacterium P. carotovorum ( Shen et al, 2021 ). In this study, the virB/D T4SS was present in the conserved genetic organization in L. enzymogenes strains CX03, CX06, M497-1 and C3, which indicated that the T4SS may play a vital role in the antagonistic activities of the bacterium; however, further studies need to explore the function of T4SS in L. enzymogenes .…”
Section: Discussionmentioning
confidence: 99%
“…The α-hydrolytic protease secreted by L. enzymogenes 3.1T8 could degrade proteins in the nematode body wall, and effectively antagonize nematode-induced plant diseases ( Folman et al, 2004 ). In addition, L. enzymogenes OH11 used the type IV secretion system (T4SS) as the main contact dependent weapon to control Pectobacterium carotovorum ( Shen et al, 2021 ). Type IV pilus-driven twitching motility, which was proven to promote bacterial colonization on host fungal surfaces in L. enzymogenes OH11, was also recognized as one of the antifungal mechanisms ( Xia et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Of those, T3SS, T4SS, and T6SS are related to the establishment of pathogenic interactions with microbial hosts in Lysobacter spp. (de Bruijn et al, 2015;Yang et al, 2020;Shen et al, 2021). Thus, modulation of genes related to secretion systems might result in gain/loss of ability to compete with other (micro)organisms (Ling et al, 2019a).…”
Section: Discussionmentioning
confidence: 99%
“…The GFP-labelled strains of B. subtilis NCD-2 and 168 were produced by early works (Dong et al 2020) and were kindly donated by Prof. Ping Ma (Hebei Academy of Agricultural and Forestry Sciences, China) and Prof. Huijun Wu (Nanjing Agricultural University, China), respectively. GFPlabelled Pseudomonas protegens Pf-5 was previously generated and storied in the laboratory (Shen et al 2021).…”
Section: Contact-dependent Killing Assaymentioning
confidence: 99%